El apoyo parental para fortalecer el rendimiento escolar en los niños de preparatoria paralelo “b” de la escuela de educación básica Filomena Mora de Carrión de la ciudad de Loja, periodo 2017-2018. - Pucha Quizhpe, Andrea Johanna (2018)
The research entitled: PARENTAL SUPPORT FOR STRENGTHENING SCHOOL PERFORMANCE AT PREPARATORY SCHOOL CLASS "B" IN CHILDREN OF THE BASIC EDUCATION SCHOOL "FILOMENA MORA DE CARRIÓN" CITY OF LOJA, PERIOD 2017-2018, had as general objective to strengthen parental support to improve school performance at high school in children of class "B" at School of Basic Education "Filomena Mora De Carrión", City of Loja during the period 2017-2018. The methods that were used were: the scientific, deductive, analytical, statistical; To obtain the information, some techniques were used, such as the survey that was applied to parents, which was reflected as a result: 40% sometimes attend the school activities of their children that the school organizes, on the other hand 60% almost always identify the knowledge, skills and attitudes with which their children must obtain at the end of the grade that they are studying, which shows that there is no adequate parental support, and as an instrument the basic functions test adaptation "REAA" to determine the school performance of the 15 children investigated. As a main result obtained from the initial test, shows that an average of 10 out of 15 children represent the 67% who find the learning areas not very stimulated, for this reason it was appropriate to apply an alternative proposal that consisted on educational workshops for parents for a period of two months with the aim of strengthening parental skills and in turn helped to improve the school performance of children, in the reevaluation of boys and girls the effectiveness was demonstrated by showing that 13 of 15 investigated children with 87% show a good command of their learning areas, the same ones that influenced in a positive way their school performance, reason why it is concluded that the elaboration and the application of this proposal is essential to strengthen the capabilities of parents and at the same time to improve the teaching-learning process of children, finally, teachers are recommended to emphasize the proposal that was implemented and apply it during the week in the classroom to improve parental skills and thus strengthen the school performance of children.